A Bibliometric Review of Nature-Based Solutions on Urban Stormwater Management - Jin Su, Jin Su; Mo Wang, Mo Wang; Mohammad Razi, Mohd Adib; Mohd Dom, Norlida; Sulaiman, Noralfishah; Lai-Wai Tan, Lai-Wai Tan (Mdpi, 2023)
: Urban stormwater management is a critical challenge facing cities globally, with naturalbased solutions (NBS) emerging as a promising approach for mitigating the impacts of urban stormwater runoff. This bibliometric review examined the research trends and hot topics related to NBS for urban stormwater management. The study utilized a combination of qualitative and quantitative methods to analyze 176 articles from the Web of Science database, covering the period from 2016 to 2022. Results showed that NBS is a widely researched topic with a growing trend in publications in recent years, led by the United States, China, and several European countries. The majority of NBS articles were research papers (82%) with a focus on environmental performance rather than social and economic dimensions. Quantitative methods were more frequently used in research articles, particularly statistical analysis/modeling. Interviews and discussions were the most common qualitative method used. The review identified the most relevant countries, affiliations, authors, and journals in the field. Furthermore, hot topics in NBS research were highlighted, including ecosystem services, climate change, and sustainability. The study also emphasized that future research perspective should focus on interdisciplinary and collaborative research, scaling up and mainstreaming NBS, and exploring new ways of integrating different disciplines and stakeholders in the research process. The findings of this review provided insights into the current state of NBS research and offer valuable information for researchers, policymakers, and practitioners in the field of urban stormwater management